Regional monitoring of the urinary tract infections causative agents antibiotic resistance in the child population of the Chernivtsi region - V. V. Bezruk; T. О. Bezruk; L. V. Stegnitska; S. O. Sokolnyk; V. V. Maksymyuk; O. I. Godovanets; O. S. Godovanets; A. I. Kovtun; M. I. Sheremet (Zaporožskij Medicinskij Žurnal)
In the scope of current medical practice the “viewpoint” regarding the growth of antibiotic resistance of microorganisms is a threat to national security. A reasonable use of antibiotics on the basis of uropathogen regional bacterial sensitivity gives the opportunity to “restrain” the growth of antibiotic resistance of microorganisms and increase the effectiveness of the UTI treatment.